Factors that influence the feasibility and implementation of a complex intervention to improve the treatment of peripheral arterial disease in primary and secondary care: a qualitative exploration of patient and provider perspectives. Issue 1 (23rd January 2023) - Le Boutillier, Clair; Saratzis, Athanasios; Saha, Prakash; Benson, Ruth; Bridgwood, Bernadeta; Watson, Emma; Lawrence, Vanessa
Abstract : Objectives: Our aim was to examine the feasibility and implementation of a complex intervention to improve the care of patients with peripheral arterial disease (the LEGS intervention) from the perspective of patients, general practitioners and secondary care clinicians. Design: A qualitative study involving semistructured individual interviews with patients and providers to gain an understanding of the feasibility of the LEGS intervention as well the barriers and facilitators to implementation in secondary and primary care. Setting: Primary and secondary care settings across two National Health Service Trusts. Participants: Twenty-five semistructured telephone interviews were conducted with (1) patients who had received the intervention (n=11), (2) secondary care clinicians responsible for delivering the intervention (n=8) and (3) general practitioners (n=6). Analysis: Data were initially analysed using inductive descriptive thematic analysis. The consolidated framework for implementation research was then used as a matrix to explore patterns in the data and to map connections between the three participant groups. Lastly, interpretive analysis allowed for refining, and a final coding frame was developed. Results: Four overarching themes were identified: (1) the potential to make a difference, (2) a solution to address the gap in no man's land, (3), prioritising and making it happen and (4) personalised information and supportive conversations for taking on the advice. The impetus for prioritising and delivering the intervention was further driven by its flexibility and adaptability to be tailored to the individual and to the environment. Conclusions: The LEGS intervention can be tailored for use at early and late stages of peripheral arterial disease, provides an opportunity to meet patient needs and can be used to promote shared working across the primary–secondary care interface.